The Importance of Internal and External Communication in Increasing Knowledge and Loyalty of Employees in Qi Malaysia - Elvina Stephanie Fernandez (Open University Malaysia, 2020)
Many organizations in Malaysia today face difficulties in retaining employees since they are unable to identify the factors that contribute to both the increase of employee knowledge on the company and loyalty towards the company. This study goes on to identify how with internal and external communications, and organisation can increase its employee’s knowledge on the company in a positive way and these better-informed employees are then more inclined to be loyal to the company. In QI Malaysia, there is at least one resignation a month and employees hardly know much about the organisation. The aim is to identify if the internal and external communications carried out did in fact help increase employee knowledge about the company and boost their loyalty in a quantitative method. The employees selected for this research received a survey form to fill independently. They were encouraged to complete the questionnaire during their break time or after work. From the response of the survey, we can understand and conclude that employees of QI Malaysia favour timely, frequent and more personal communication through internal communications and external communications methods. They are happy to know that through the internal communications that they are remembered by the company top level management and that their company is portrayed as an employer of choice, leading to individuals they know wanting to work in QI Malaysia. As recommendation, it is suggested that more content about the company is sent out through both internal and external communication of choice, in this case, mass mails being internal communication channel and Facebook as the external communication channel as most employees are engaged here. With more related contents through these two platforms, it will encourage engagement that will increase employee knowledge and loyalty towards the company. (Abstract by author)